Journal of Instrumentation - Kube, G. (2018)
Coherent transition radiation (CTR), produced by short electron bunches, is a wellknown radiation mechanism which is applied for bunch length monitoring. By analyzing the CTR spectrum it is possible to reconstruct the longitudinal bunch shape. Such a technique is widely used for accelerators with electron beams possessing bunch lengths Coherent transition radiation (CTR), produced by short electron bunches, is a wellknown radiation mechanism which is applied for bunch length monitoring. By analyzing the CTR spectrum it is possible to reconstruct the longitudinal bunch shape. Such a technique is widely used for accelerators with electron beams possessing bunch lengths [sigma]z much larger than their transverse beam sizes [sigma]x,y (with [sigma]x,y,z the rms transverse and longitudinal beam sizes). New developments in the field of accelerator technology allow to produce and accelerate bunches with a duration of less than 1 fs with a "pancake-like" bunch shape, i.e. with [sigma]z [sigma]x,y. Diagnostic schemes of this kind of bunches give rise to interesting effects, for example connected with a transverse asymmetry ([sigma]x , [sigma]y), with a tilting of the bunches (i.e. the bunch axis does not coincide with the velocity direction), and even more. Spectral-angular distributions of coherent backward transition radiation (BTR) were simulated taking into account a possible bunch tilt. It is shown that spectral intensity measurements of coherent BTR emitted in backward direction allow to obtain information about the bunch length.